Pengaruh Kinerja Corporate Social Responsibility (CSR) Terhadap Persistensi Laba pada Perusahaan yang Bergerak di Sektor Barang Konsumsi Dengan Sub Sektor Rokok, Makanan dan Minuman di Indonesia - Lily Iman Wijaya (Business Accounting Review, 2016)
Researches that connecting Corporate Social Responsibility (CSR) with sustainable performance are still very rare. Among them were Laksmana and Yang (2009), Belkaoui (2004), Lassaad and Khamoussi (2013). On the other hand, the succesful implementation of CSR could not be measured by periodic financial performance but measured by sustainable performance, that is earning persistence. Therefore, this study was conducted to determine the influence of CSR to the earning persistence.This study used samples start from 2010 until 2014 with 14 companies by using control variables Operating cycle, Sales volatility, Cash flow volatility and Negative earning. This study used SPSS version 22 as a measuring tool. This study has not succeeded yet able to prove the positive influence of CSR to earning persistence, and found negative influence between sales volatility to earning persistence.